2017
DOI: 10.1186/s13148-017-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

BNDF methylation in mothers and newborns is associated with maternal exposure to war trauma

Abstract: BackgroundThe BDNF gene codes for brain-derived neurotrophic factor, a growth factor involved in neural development, cell differentiation, and synaptic plasticity. Present in both the brain and periphery, BDNF plays critical roles throughout the body and is essential for placental and fetal development. Rodent studies show that early life stress, including prenatal stress, broadly alters BDNF methylation, with presumed changes in gene expression. No studies have assessed prenatal exposure to maternal traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 98 publications
(124 reference statements)
1
56
0
Order By: Relevance
“…A wide body of evidences indicates the exposure to stressful events in adulthood changes DNAm in rodent brains. Several clinical studies have suggested the possibility that stressful events can alter DNAm of the BDNF gene in blood or brain . For example, we previously reported that DMRs in 28 of 35 CpG units at CpG I of the BDNF gene in blood were changed in unmedicated patients with major depression as compared with healthy subjects .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A wide body of evidences indicates the exposure to stressful events in adulthood changes DNAm in rodent brains. Several clinical studies have suggested the possibility that stressful events can alter DNAm of the BDNF gene in blood or brain . For example, we previously reported that DMRs in 28 of 35 CpG units at CpG I of the BDNF gene in blood were changed in unmedicated patients with major depression as compared with healthy subjects .…”
Section: Discussionmentioning
confidence: 95%
“…Several clinical studies have suggested the possibility that stressful events can alter DNAm of the BDNF gene in blood or brain. 33,34,40,41 For example, we previously reported that DMRs in 28 of 35 CpG units at CpG I of the BDNF gene in blood were changed in unmedicated patients with major depression as compared with healthy subjects. 28 Keller et al 42 reported that DMRs at the promoter of exon IV of the BDNF gene in the Wernicke area of subjects who had committed suicide Some limitations of the current study warrant mention.…”
Section: Dmrs Of the Bdnf Gene On Cognitive Impairmentmentioning
confidence: 99%
“…For example, BDNF is hypermethylated not only in mothers exposed to war trauma, but also in their new-born infants 29 and increased methylation of BDNF promoter is associated with conversion of amnestic mild cognitive impairment to Alzheimer disease. This is an area only recently starting to be explored, but one focus has been brain-derived neurotrophic factor.…”
Section: Neurodevelopment Neurodegeneration and The Epigenomementioning
confidence: 99%
“…This is an area only recently starting to be explored, but one focus has been brain-derived neurotrophic factor. For example, BDNF is hypermethylated not only in mothers exposed to war trauma, but also in their new-born infants 29 and increased methylation of BDNF promoter is associated with conversion of amnestic mild cognitive impairment to Alzheimer disease. 30 The genetics of Alzheimer disease is complex and, no doubt, the epigenetics is as well.…”
Section: Neurodevelopment Neurodegeneration and The Epigenomementioning
confidence: 99%
“…In this context, those individual soldiers who carried one or two low functioning alleles (the S or LG allele) reported enhanced symptoms of PTSD, depression and anxiety in response to increased levels of exposure to war zone stressors, relative to soldiers homozygous derived from the high functioning allele (LA allele). In a study of Among 24 mothers and newborn infants in the eastern Democratic Republic of Congo, a region afflicted by long-lasting, extreme conflict conditions of violence towards women and children, it was shown that the maternal experiences of war trauma and chronic stress were associated with BDNF methylation in umbilical cord blood, placental tissue, and maternal venous blood [29]. These linkages of maternal stress and BDNF methylation were associated with high tissue specificity with significant associations observed in the putative transcription factor binding regions of these individuals; a notable demonstration of detrimental epigenetic changes with long-lasting, trans-generational consequences.…”
Section: Introductionmentioning
confidence: 99%